Analysis of diversity of chromophytic phytoplankton in a mangrove ecosystem using rbcL gene sequencing. Issue 2 (15th February 2014) - Samanta, Brajogopal; Bhadury, Punyasloke; Mock, T.
<x xml:space="preserve">Abstract</x> Phytoplankton forms the basis of primary production in mangrove environments. The phylogeny and diversity based on the amplification and sequencing of rbcL, the large subunit encoding the key enzyme ribulose‐1, 5‐bisphosphate carboxylase/oxygenase was investigated for improved understanding of the community structure and temporal trends of chromophytic eukaryotic phytoplankton assemblages in Sundarbans, the world's largest continuous mangrove. Diatoms (Bacillariophyceae) were by far the most frequently detected group in clone libraries (485 out of 525 clones), consistent with their importance as a major bloom‐forming group. Other major chromophytic algal groups including Cryptophyceae, Haptophyceae, Pelagophyceae, Eustigmatophyceae, and Raphidophyceae which are important component of the assemblages were detected for the first time from Sundarbans based on rbcL approach. Many of the sequences from Sundarbans rbcL clone libraries showed identity with key bloom forming diatom genera namely Thalassiosira, Skeletonema and Nitzschia. Similarly, several rbcL sequences which were diatom‐like were also detected highlighting the need to explore diatom communities from the study area. Some of the rbcL sequences detected from Sundarbans were ubiquitous in distribution showing 100% identities with uncultured rbcL sequences targeted previously from the Gulf of Mexico and California upwelling system that are geographically separated from study area. Novel rbcL lineages were also detected highlighting the need to culture and sequence phytoplankton from the ecoregion. Principal component analysis revealed that nitrate is an important variable that is associated with observed variation in phytoplankton assemblages (operational taxonomic units). This study applied molecular tools to highlight the ecological significance of diatoms, in addition to other chromophytic algal groups in Sundarbans.